THE EFFICACY OF TENDERING PROCESS ON OUTSSOURCED REVENUE COLLECTION IN LOCAL GOVERNMENTS IN TANZANIA: EXPERIENCE FROM SELECTED LOCAL GOVERNMENT COUNCILS - Mtasigazya, Paul (PEOPLE: International Journal of Social Sciences, 2019)
This paper broadly investigated the efficacy of tendering process on outsourced revenue collection in Kinondoni Municipal Council (KMC) and Morogoro Municipal Council (MMC) in Tanzania. The objective of this study was to examine how tendering process was effective on outsourced revenue collection in KMC and MMC. The study adopted the case study research design and the methods of data collection were interviews and documentary review. The findings indicate that the tendering of revenue collection was futile because the criteria for selecting the bidders were not transparent due to the fact that tenders were not advertised by MMC and MMC in widely circulated media, as such they could not be accessed by some of the prospective bidders in studied councils. The tenders were offered to companies lacking the required criteria, such as resources, and so were unable to fulfil their contractual obligations after being selected to collect revenue in KMC and MMC. It therefore concluded that ineffectiveness of the tendering process in MMC and KMC resulted in awarding tenders to Companies lacking the required capacity to collect revenue which consequently contributed to dismal revenue collection in studied Councils. This study recommends that Councils should consider the merit of the companies in awarding tenders for revenue collection and comply to Public Procurement Act No.7 of 2011.